Explore BrainMass

Explore BrainMass

    Equality of gcd's

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Show that if gcd(a, b) = 1, then gcd(ac, b) =gcd(b, c).

    © BrainMass Inc. brainmass.com November 30, 2021, 1:09 am ad1c9bdddf
    https://brainmass.com/math/graphs-and-functions/equality-gcds-85988

    Solution Preview

    Proof:
    Let x=gcd(ac,b), y=gcd(b,c).
    First, since y=gcd(b,c), then y|b, y|c, so y|ac, thus y is a ...

    Solution Summary

    This solution is comprised of a detailed explanation to show that if gcd(a, b) = 1, then gcd(ac, b) =gcd(b, c).

    $2.49

    ADVERTISEMENT